Islamic financial literacy and management for MSMEs - Imam Suseno; Larisa Yohanna; Endang Sondari (President University, 2022)
The Financial Services Authority Indonesia (OJK) survey has been released, that the financial literacy rate of Indonesian people. The OJK is classified aproximatelly 29.7%, which is considered well literature. Low financial literacy and its products cause people, especially MSMEs, to be easily caught up in lucrative short-term investments without considering the risks faced later on. The low financial literacy for MSMEs is also due to the lace of knowledge and attitudes towards Islamic financial institutions in Indonesia which are the pillars of the national economy. This research aims to reveal the level of Islamic financial literacy and financial management of Sharia for SMEs. The research approach utilizes a descriptive quantitative. The researchers use questioner, in-depth interviews, and field observations as their data. The data is taken in June-August 2021. The respondents, who are associated with the OKe Oce organization, is located in Kuningan-West Java, Jakarta, and Surabaya-East Java, and are selected randomly. The research results show: (1) The level of Islamic financial literacy of MSME actors is mostly at the level of less less literate, (2) Financial management of MSME actors is still not ideally organized and runs professionally, and (3) there are three pillars of increasing Islamic financial literacy: promotions/campaigns, strengthening the Islamic financial literacy infrastructure, and Structuring/services the Islamic finance industry properly. MSME actors must be convinced that transacting with Islamic financial institutions can improve their welfare based on sharia principles that are halal and profitable.